2008
DOI: 10.1227/01.neu.0000316414.20247.32
|View full text |Cite
|
Sign up to set email alerts
|

Expanded Endoscopic Endonasal Approach for Treatment of Clival Chordomas

Abstract: The expanded endoscopic endonasal approach is a valid minimally invasive alternative for the treatment of centrally located clival chordomas or as an adjunct for the central part of chordomas with lateral extension. The early results of this technique indicate at least equivalency to more extensive open approaches, and its versatility may widen the horizon of surgical management of these aggressive lesions. The challenge with the cerebrospinal fluid leakage is being addressed with novel local flap repair techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
97
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(109 citation statements)
references
References 39 publications
5
97
0
7
Order By: Relevance
“…1,5,9,20 This EEA shows almost equivalent results to extensive approaches. 21,22 The complication of CSF leak can be managed with local flap repair techniques. Hence, this approach should be in the surgery of choice for the management of clival chordomas.…”
Section: 12mentioning
confidence: 99%
See 1 more Smart Citation
“…1,5,9,20 This EEA shows almost equivalent results to extensive approaches. 21,22 The complication of CSF leak can be managed with local flap repair techniques. Hence, this approach should be in the surgery of choice for the management of clival chordomas.…”
Section: 12mentioning
confidence: 99%
“…[20][21][22] Conventional radiotherapy with high-energy photons at a dose of 60 to 65 Gy may offer temporary benefit in disease control in patients with inadequate surgery or recurrence or as exclusive treatment for inoperable disease. 22 Prognosis of the tumor is typically poor, due to the locally aggressive nature of these tumors, with the 10-year survival approximately 40%. 2,17,22 …”
Section: 12mentioning
confidence: 99%
“…For example, Fraser et al [ 44 ] achieved > 95% tumor resection in seven (87%) of eight patients in whom complete tumor resection was the goal. Stippler et al [ 117 ] and Dehdashti et al [ 27 ] reported GTR resection rates for clival chordomas of 67% and 58% with CSF leak rates of 25% and 33%, respectively. Carrabba et al [ 11 ] found reduced levels of postoperative morbidity in patients treated via an endonasal endoscopic approach for clival lesions as compared to those who underwent open resection.…”
Section: Clival Chordomasmentioning
confidence: 99%
“…1 The expanded endonasal approach (EEA) and its modifications provide access to the anterior skull base, planum, sphenoid, sella, clivus, cervical spine, and infratemporal fossa via the two nostrils. [2][3][4][5][6][7][8][9] This approach enables endoscopic extradural and intradural tumor resection and skull base reconstruction in a single procedure.…”
Section: Introductionmentioning
confidence: 99%